Doctors' views on the quality of claims provided by pharmaceutical representatives: A comparative study in Malaysia and Australia - Noordin Othman; Agnes I. Vitry; Elizabeth E. Roughead; Shaiful B. Ismail; Khairani Omar (Elsevier Ltd, 2024)
Indexed by Scopus